Analysing Metacognitive Strategies Used in Reading Scientific Article: A Case Study of EFL University Students - Elda Yulia Ryandini; Dias Tiara Putri Utomo; Pipit Ertika Daristin (Universitas Islam Negeri Palopo, 2025)
In the process of reading, students have to be aware, think about what difficulties they always encounter, and think about the strategies used in reading, known as metacognitive awareness. Hence, this study is necessary to analyze students’ perceptions about reading in English and their ways to cope with the problems by assessing their own metacognitive strategies. This study applies a case study of a qualitative approach with 39 first-year EFL university students. The results indicate that 58.97% of students like reading because it can boost their understanding of vocabulary, sentence structure, language skills, academic achievement, and speaking English properly. There are no difficulties encountered in reading English since it is fun, easy to understand, and gives them new knowledge. While the rest, 41.02% of students, explained different experiences since they perceived reading English as boring and a bit difficult in the case of pronunciation and words, but it is needed in students’ jobs. While the most frequent strategies used in metacognitive awareness of reading are